OUTCOMES OF ANTI-VEGF THERAPY IN CHOROIDAL NEOVASCULARIZATION AFTER MACULAR SURGERY. Issue Volume 12:Issues 4(2018) (2018) - Hua, Duc Anh; Casella, Antonio M.; Berrocal, Maria H.; Han, Dennis; Alshareef, Rayan A.; Quiroz-Mercado, Hugo; Arevalo, J. Fernando; Chhablani, Jay
Abstract : Purpose: To report treatment outcomes of anti-vascular endothelial growth factor (VEGF) therapy in choroidal neovascularization (CNV) presenting after macular surgery. Methods: Retrospective analysis of 7 eyes of 7 patients, who were diagnosed to have CNV after macular surgery and were treated with anti-vascular endothelial growth factor therapy. Collected data included demographic details; history of present illness; surgical procedure; and clinical examination including visual acuity at presentation and follow-up with imaging and management. Main outcome measures were resolution of CNV activity at the last follow-up. Secondary outcomes included change in visual acuity at final follow-up from baseline, number of injections, treatment free interval, and adverse events. Results: Seven eyes of 7 patients (2 females and 5 males), which underwent macular surgery (4 macular hole repairs and 3 epiretinal membrane (ERM) removal), were included in this study. Two eyes had drusen at the time of surgery; however, five eyes had no preexisting conditions. Mean interval between surgery and CNV development was 21.07 ± 38.55 months (range, 2 months–9 years). All patients had undergone intravitreal anti-vascular endothelial growth factor injections (range, 2–15; mean number: 5.85) with one eye requiring additional photodynamic therapy (PDT) and focal laser. Visual acuity was unchanged with inactive CNV at the last visit in all eyes after anti-vascular endothelial growth factor therapy. The mean follow-up duration after the development of CNV was 35.5 months (range, 6.5 months–8 years). Conclusion: Choroidal neovascularization occurring after otherwise successful macular surgery is uncommon with unknown predisposing factors. This entity appears to have poor visual outcome with currently available anti-vascular endothelial growth factor therapy. Abstract : Choroidal neovascularization after macular surgery is very rare. Treatment outcome with anti-vascular endothelial growth factor therapy is poor irrespective of preexisting conditions.